(untitled) (Agricultural Engineering, 2016)
The objective of the paper was to know preferences of consumers from Małopolskie Voivodeship as a fundamental factor of growth and functioning of distribution channels of organic products. A fast development of the organic products market as well as growing requirements of the society with regard to the quality of sale and form are observed. More and more often consumers pay attention to the source of goods and the form in which the product is offered to them. Research and analyses are a precious source of information for agricultural producers on account of production orientation and the form of sale. It will also facilitate development of existing distribution channels and formation of new ones. Research results indicate that consumers are interested in the purchase of products in small packaging or loose. Sums which they spend on organic food do not exceed PLN 400 per a month.